Five-year outcomes of percutaneous coronary intervention using second generation drug-eluting stents for multivessel coronary artery revascularisation - Sahue, A.; Prakaschandra, D.R.; Patel, J.J.; Naidoo, D.P. (SA Heart Journal, 2025)
Aim: This report evaluated outcomes of percutaneous coronary intervention (PCI) using drug-eluting stents (DESs) compared to coronary artery bypass grafts (CABG) for multivessel coronary artery disease (CAD). Methods: Sixty patients (43M, 17F); mean = 64.35 years (SD ± 10.4) who underwent PCI or CABG were followed up for 5 years. Revascularisation included 19 elective and 5 emergency cases. The composite outcome (defined as major adverse cardiac and cerebral events [MACCE]), and rates of repeat revascularisation were compared in each group using survival curves and adjusted Cox pro-portional hazard models. Results: Nine (15%) patients sustained acute MI and 6 (10%) suffered a stroke during follow-up (PCI n=5, CABG n=4). There were 10 deaths (DVD n=2, TVD n=8) (6 CABG, 4 PCI). There was no difference in treatment effects between the 2 groups for time to MI, stroke, and angina (PCI 40% vs. CABG 23.3%, p=0.194). Adjusted 5-year risk of death (11.7% vs. 17.6%, OR=1.300, CI=0.313 - 5.404, p=1.000) and the composite of death, stroke and MI (51.3% vs. 44% p=0.566) were similar in the 2 groups. There was a higher rate of repeat revascularisation in PCI group (52.8% vs. 29.3%) (p=0.121.) Conclusions: PCI using DESs for patients with multivessel CAD showed similar outcomes to CABG.